A Metadata Manifesto: The Need for Global Health Metadata - Fabreau, Gabriel E; Minty, Evan P; Southern, Danielle A; Quan, Hude; Ghali, William A (International Journal of Population Data Science, 2018)
Administrative health data recorded for individual health episodes (such as births, deaths, physician visits, and hospital stays) are being widely used to study policy-relevant scientific questions about population health, health services, and quality of care. Furthermore, an increasing number of international health comparisons are being undertaken with these data. An essential pre-requisite to such international comparative work is a detailed characterization of existing international health data resources, so that they can be more readily used in comparison studies across counties. A major challenge to such international comparative work is the variability across countries in the extent, content, and validity of existing administrative data holdings. Recognizing this, we have undertaken an international pilot process of compiling detailed data about data – i.e., a “meta-data catalogue” – for existing international administrative health data holdings. The methodological process for collecting these meta-data is described here, along with some general descriptive results for selected countries included in the pilot.